Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Publication Title: SOOS Report Series Volume: 9
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Hva skjer med klimaet i polarområdene? : sammendrag av foredrag på symposium 25-26 april 1989 - Orheim, Olav (ed.); Brekke, Annemor (ed.) (Norsk Polarinstitutt, 1989)
Publication Title: Norsk Polarinstitutt. Rapportserie
Keywords: Antarktis; global oppvarming; klimaendringer; polarområdene; symposium

Sea bed feauters in the Blåenga area, Weddell Sea, Antarctica - Lien, Reidar (Université Laval, 1981)
Pages: 706-716 Publication Title: POAC 81 : The Sixth International Conference on Port and Ocean Engineering under Arctic Conditions Volume: 2 Place: Quebec, Canada
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; geologi; havbunnen; kongress; oseanografi; symposium

The work of SCAR for the conservation of nature in the Antarctic - Gjelsvik, Tore (University of Chile, 1977)
Pages: 328-334 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; fauna; flora; forurensning; kongress; miljø; politikk; symposium; økologi

Global glacier mass balance variations during the past 300 years - Orheim, Olav (Arctic Institute of North America, 1977)
Pages: 667-681 Publication Title: Polar Oceans Place: McGill University, Montreal, Canada
Keywords: Antarktis; glasiologi; is; isbreer; klimaendringer; konferanse; polarområdene; stratigrafi; symposium

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Pages: 154-160 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium

Antarctic geology and geophysics : symposium on Antarctic Geology and Solid Earth Geophysics : Oslo, 6-15 August 1970 - Adie, Raymond J. (Universitetsforlaget, 1972)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Report on attendance at the Second Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6 to 15 August, 1970 - Kent, L E (Geological Survey of South Africa, 1971)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium